Urgensi Literasi Budaya dan Kewarganegaraan di Sekolah Dasar Dalam Upaya Mencintai Tanah Air - Serli Malini; Dinie Anggraeni Dewi; Rizky Saeful Hayat (Jurnal Multidisiplin Indonesia, 2023)
Mastery of cultural and civic literacy is important in the 21st era. Indonesia has a diversity of tribes, languages, customs, beliefs and social layers. Currently, changing times continue to take place along with the progress of globalization which requires all aspects of life to adapt. This globalization easily spreads to every country, including Indonesia. The impact is seen in various things that are influenced by or originate from this global progress. Today's life requires every individual to change the way they view other people. Views that are not in line with the flow of global progress can lead individuals to misguidance and even alienation at home. From here, various problems arise, especially the decline in love for the homeland. This research aims to find ways to address the importance of cultural and civic literacy in strengthening feelings of love for the homeland. The research method used is a literature study with a qualitative approach. The data used comes from primary and secondary sources, such as books, e-books, e-journals and articles. The results of the research show that many Indonesian people still prefer and like foreign films, for example from South Korea, Japan, China and Thailand. This reduces their love for their homeland because they tend to be reluctant to choose films that are their own cultural heritage.